Scheduling Preventive Maintenance to Determine Maintenance Actions on Screw Press Machine - Ferdi Pohan; Imam Saputra; Rahmat Tua (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
PT. PAS is a company engaged in the manufacturing industry, is a company that manages palm oil into Crude Palm Oil (CPO) and Palm Kernel (PK) with a capacity of 30 tons/hour. The method used in this study is Relia-bility Centered Maintenance (RCM). This method can determine the actions of preventive maintenance activi-ties on each component of the screw press machine. This study aims to provide proposals for scheduling pre-ventative Maintenance of screw press machines using the Reliability Centered Maintenance (RCM) approach and determine appropriate maintenance actions in damage prevention. Based on the results of the research con-ducted, it can be concluded that in the Reliability Centered Maintenance (RCM) approach, it is known that five types of damage are a priority for repair. The types of damage included in the repair priority are worm screws, extension shafts, bearings, press cages, and oil seals. The proposed maintenance time for each critical compo-nent is a worm screw component maintenance time interval of 307.84 hours, and changeover schedules every 2035.3 hours. Component extension shaft maintenance time interval 279.5 hours, changeover schedule every 1824.5 hours. Bearing components have a maintenance time interval of 300.2 hours and a changeover schedule of every 1492.5 hours. Oil seal components maintenance time interval 286.1 hours, changeover schedule every 2769.9 hours. Press cage components maintenance time interval 250.72 hours, changeover schedule every 3277.8 hours. Actions are taken in the form of direct prevention of the source of component damage based on the time or age of the component.